Improving the Nutritional Status of Pregnant Women Who Experience Chronic Energy Deficiency with Spirulina Platensis - Finta Isti Kundarti; Ira Titisari; Kiswati; Dwi Estuning Rahayu; Bastianus Doddy Riyadi (KHD Production, 2024)
The highest prevalence of chronic energy deficiency (CED) in pregnancy occurs in the third trimester of pregnancy. The impacts that occur are abortion, premature birth, premature rupture of membranes, histitis, postpartum hemorrhage, and low birth weight (LBW). To prevent negative impacts, giving Spirulina Platensis is believed to improve nutritional status. This study aimed to analyze the effect of spirulina platensis extract on improving nutritional status in pregnant women. Using a Quasi-Experiment with a pretest and posttest control group design with a sample of 60 participants consisting of an intervention group of n=30 participants and a control group of n=30 participants. The intervention group received treatment, namely being given Spirulina Platensis extract, 1 capsule containing 300 mg, taken once for 30 days and standard care, while the control group received standard care only. The sampling technique used was simple side random. Chi-Square test results in the intervention group mean pretest nutritional status (m=22.04, SD=1.170) and posttest (m=23.33, SD=0.922) p-value=0.000, while the control group showed pretest nutritional status (m=22.16, SD=1.104) and posttest (m=22.39, SD=1.016) p-value=0.150. The difference between the mean posttest nutritional status in the experimental and control groups shows (m=23.33, SD=0.922) vs (m=22.39, SD=1.016) p-value=0.000. There is an increase in the administration of Spirulina Platensis extract on the nutritional status of pregnant women. As input for health workers, especially midwives, to provide non-pharmacological therapy to pregnant women who experience chronic energy deficiency (CED) by administering Spirulina Platensis.